Covid-19 Pandemic as Behaviour Awareness-Tourism - Intan Widuri Sakti; Mohd Haizam Saudi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The conditions Covid-19 pandemic have caused massive changes, and this has an effect on consumer behavior. Several dominant behaviors appear in generally. This is what will be the reference material for research, whether this behavior also appears in the tourism industry, or is there any other behavior found from the results of this research. This will be tested through the variables that are used as research tool, using travel intentions, digital marketing, and tourist’s perceived risks.